VD_FINDINFO AI 155/10 - 563/2011 vom 27. Oktober 2011 - VD Tribunal cantonal (2011)
DEGRÉ DE L'INVALIDITÉ, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, PRESTATION D'INVALIDITÉ | 28 LAI, 4 LAI, 6 LPGA, 7 LPGA, 8 LPGA